The contextual adaptation and educational impacts of the mhGAP-IG to address child mental and behavioral disorder treatment gap in China: A mixed-method study - Meng Zheng; Yi Zhang; Feng Chen; Ang Chen; Di Kong; Kun Xie; Jie Li; Brian James Hall; Andre M.N. Renzaho; Jian-hui Gao; Dao-meng Cheng; Qing Zou; et al. (SSM - Mental Health)
The Mental Health Gap Action Program Intervention Guide (mhGAP-IG) is an international evidence-based intervention to enhance the scalability of non-specialized workforce to address mental, neurological, and substance use disorders, including child mental and behavioral disorders (CMBDs). Implementation in China remains limited. This study sought to adapt the CMBDs-related components of the mhGAP-IG to the local context and assess the educational impacts of the adapted CMBDs-mhGAP-IG in non-specialized settings in Guangdong Province, China. Contextual adaptation was conducted through a four-step process guided by the Consolidated Framework for Implementation Research (CFIR) and the Ecological Validity Model (EVM). Qualitative data were collected via key informant interviews with six mental health experts and two focus group discussions involving seven kindergarten teachers or doctors and six general practitioners (GPs) from primary care centers. A qualitative analysis utilizing deductive and inductive thematic coding was applied. The educational impacts of a two-day training based on the adapted CMBDs-mhGAP-IG were assessed using a pre-post design among 89 participants, including kindergarten teachers or doctors and GPs. Changes in knowledge and stigma toward CMBDs were analyzed using paired t-tests. Qualitative findings identified barriers and facilitators to implementation across four CFIR domains: intervention characteristics, outer setting, inner setting, and characteristic of individuals. Barriers were concentrated in intervention characteristics (e.g., complexity, time and labor costs) and outer setting (e.g., stigma, high treatment cost). Contextual adaptation based on EVM addressed many of these barriers. Quantitative results indicated that the adapted CMBDs-mhGAP-IG training was associated with increased knowledge and reduced stigma toward CMBDs, demonstrating its educational effectiveness. This study identified barriers and facilitators to mhGAP implementation and documented a contextual adaptation process, offering insights into integrating contextual adaptation methods with implementation science. Trainings based on the adapted mhGAP-IG for non-specialists improved knowledge and stigma toward CMBDs, laying the foundation for future effectiveness evaluations.